2013
DOI: 10.1186/1556-276x-8-12
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a CO and NH3 gas mixture using carboxylic acid-functionalized single-walled carbon nanotubes

Abstract: Carbon nanotubes (CNT) are extremely sensitive to environmental gases. However, detection of mixture gas is still a challenge. Here, we report that 10 ppm of carbon monoxide (CO) and ammonia (NH3) can be electrically detected using a carboxylic acid-functionalized single-walled carbon nanotubes (C-SWCNT). CO and NH3 gases were mixed carefully with the same concentrations of 10 ppm. Our sensor showed faster response to the CO gas than the NH3 gas. The sensing properties and effect of carboxylic acid group were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…At this stage, based on what is known in the literature, we can state the following possibilities for the sensing mechanism. COOH-functionalized nanotubes have been widely used as sensing material for sensing NH 3 , Cl 2 , and CO (Dong et al, 2013;Robinson et al, 2006). As reported by Robinson et al (2006), the defect sites serve both as low-energy adsorption sites and as nucleation sites for additional condensation of the analyte on the surface of the nanotubes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, based on what is known in the literature, we can state the following possibilities for the sensing mechanism. COOH-functionalized nanotubes have been widely used as sensing material for sensing NH 3 , Cl 2 , and CO (Dong et al, 2013;Robinson et al, 2006). As reported by Robinson et al (2006), the defect sites serve both as low-energy adsorption sites and as nucleation sites for additional condensation of the analyte on the surface of the nanotubes.…”
Section: Resultsmentioning
confidence: 99%
“…Sulfonic acids are much stronger acids than the corresponding carboxylic acids. -SO 3 H is also an electron withdrawing group similar to the -COOH group and, therefore, it is reasonable to consider that the sulfonic acid groups introduced on the surface cause an enhancement of charge density in the SWCNTs; this can increase the amount of electron transfer between sulfonated SWCNT and CO molecules, which increases the hole current of p-type sulfonated SWCNT (Dong et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to outstanding chemical stability [18] and electrical properties [19], some carbon nanotube-based sensors have exhibited detection limit as low as 10ppb (parts per billion) [20] and shown a very high selectivity towards target gases [21]. For instance, singlewalled carbon nanotube (SWCNT)-based gas sensors were shown to detect target gases such as CO or NH 3 [2224], and multiwalled carbon nanotube-based (MWCNT) sensors were used to successfully detect H 2 S, CHCl 3 , and ethanol [18,25,26]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, oxygen is still needed to recover this material following H 2 S exposure, meaning that this sensor can only operate in oxygen-rich conditions. At the same time, it has been suggested that oxygen may not be necessary to recover the sensing ability of acid-treated carbon nanotubes [22]. Specifically, the resistance change in carboxylic acid-modified carbon nanotubes could be due to the weak hydrogen bonds formed between carboxylic acid groups on the carbon nanotube surface and H 2 S, which can change charge distribution of the carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Karimi et al proposed an analytical model of graphene-based solution-gated (SG) FETs to constitute an important step towards development of DNA biosensors with high sensitivity and selectivity [6]. Dong et al fabricated carbon monoxide (CO) and ammonia (NH 3 ) gas sensors using interdigitated electrodes on Si wafer, and they found that 10 ppm of CO and NH 3 could be electrically detected using a carboxylic acid-functionalized single-walled carbon nanotube (C-SWCNT) [7]. …”
Section: Introductionmentioning
confidence: 99%